2018
DOI: 10.1007/s00431-018-3173-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social inequalities on children’s knowledge and representation of health and cancer

Abstract: Reducing inequalities in the field of cancer involves studying the knowledge and mental representations of cancer among children. A qualitative study was conducted on 191 children aged 9 to 12 using the “write and draw” technique to get spontaneous mental representations of “healthy things”, “unhealthy things” and “cancer”. We grouped the voluntary schools according to two deprivation levels. In response to the request to “write or draw anything you think keeps you healthy”, the main responses categories were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Lockhart and Keil (2018) also found that by age 10, children understand the agency of medication for various illnesses and have a tempered optimism closer to adults than younger children. The emergence of a finer understanding of cancer for children in middle childhood has also been shown in several qualitative studies (Denois et al, 2018;Karabudak et al, 2019;Knighting et al, 2011). Therefore, the sample of the current study included fourth-and fifth-grade children.…”
Section: Knowledge Of Cancermentioning
confidence: 71%
“…Lockhart and Keil (2018) also found that by age 10, children understand the agency of medication for various illnesses and have a tempered optimism closer to adults than younger children. The emergence of a finer understanding of cancer for children in middle childhood has also been shown in several qualitative studies (Denois et al, 2018;Karabudak et al, 2019;Knighting et al, 2011). Therefore, the sample of the current study included fourth-and fifth-grade children.…”
Section: Knowledge Of Cancermentioning
confidence: 71%